Application of a macrocyclization strategy in kinase inhibitor development - Kun Xing; Shujun Li; Jinghuan Li; Dan Liu; Min Huang; Linxiang Zhao (Acta Materia Medica, 2025)
Kinases have a pivotal role in phosphorylation and kinase dysregulation has been implicated in the occurrence and progression of various diseases. By mid-2024 the Food and Drug Administration had approved 81 small-molecule kinase inhibitors targeting greater than 30 kinases, providing substantial clinical benefits for patients with cancer and other diseases. However, many reported kinase inhibitors exhibit poor target selectivity, limited solubility, and issues with drug resistance. To address these challenges medicinal chemists have used a macrocyclization strategy to optimize these molecules and three macrocyclic kinase inhibitors (lorlatinib [ALK/ROS1], pacritinib [Flt3/JAK2], and repotrectinib [TRK/ROS1]) have received FDA approval. The macrocyclization strategy is now widely used to enhance kinase inhibitory activity, overcome drug resistance caused by point mutations, improve kinase selectivity, and optimize drug-like properties. In this review we provide a comprehensive overview of the utilization of macrocyclization in the optimization of kinase inhibitors by detailing the structural modification process from lead compounds to macrocyclic molecules that has been applied in recent years. In addition, we discuss the limitations of existing macrocyclic kinase inhibitors and propose key considerations for the development of improved macrocyclic molecules. We aim for this review to offer valuable insights for future advances in kinase inhibitor development.